AI empowers the high-quality development of financial and economic college education: opportunities, dilemmas and solutions - Wang, Jing; Su, YunNan; Guo, MengXin (IC-ITECHS, 2024)
With the development of the digital economy, AI has gradually given full play to its advantages, improved the overall development of the financial industry, and enhanced the momentum of the industry. For college students in the contemporary financial industry, it is both an opportunity and a challenge. On the basis of analyzing the changes in the financial industry, this paper puts forward the corresponding measures that college students should take for the reference of relevant personnel